Dynamic Effects of Immersive Bilingualism on Cortical and Subcortical Grey Matter Volumes - Marin-Marin, Lidón; Costumero, Victor; Ávila, César; Pliatsikas, Christos (Frontiers in Psychology, 2022)
Bilingualism has been shown to induce neuroplasticity in the brain, but conflicting evidence regarding its specific effects in gray matter continues to emerge, probably due to methodological differences between studies, as well as approaches that may miss the variability and dynamicity of bilingual experience. In our study, we devised a continuous score of bilingual experiences and we investigated their non-linear effects on regional GM volume in a sample of young healthy participants from an immersive and naturalistic bilingual environment. We focused our analyses on cortical and subcortical regions that had been previously proposed as part of the bilingual speech pipeline and language control network. Our results showed a non-linear relationship between bilingualism score and grey matter volume of the inferior frontal gyrus. We also found linear increases in volumes of putamen and cerebellum as a function of bilingualism score. These results go in line with predictions for immersive and naturalistic bilingual environments with increased intensity and diversity of language use and provide further evidence supporting the dynamicity of bilingualism’s effects on brain structure.